Amaurosis secondary to sphenoid mucocele - Melo, Antonio Antunes; Neto, Sílvio da Silva Caldas; Gouveia, Mariana Carvalho Leal; Santos, Patrícia Ferreira (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The mucocele of the sphenoide sinus its a benign rare lesion. Those lesions are probably diagnosed late because they are asymptomatic or cause non-specific symptoms. The clinical characteristics depend on its location and can include fronto-orbital pain, oculomotor nerve palsy, decrease of visual acuity, exophthalmos and olfaction disorders. The findings of the CT and the MRI of nose and paranasal sinuses have increased the diagnostic accuracy. The treatment consists of marsupialization and drainage of the mucocele via endoscopic sinus. The prognosis for vision depends on the length loss of the visual acuity preoperative.Objective: Report a case of sphenoid mucocele of big dimensions.Case Report: The authors report a case of sphenoid sinus mucocele in a male patient of 48 years old, that has suddenly presented amaurosis.Final Comments: The caracteristics of the sphenoid mucocele are reviewed with special attention for the clinical and radiological findings, as well as the surgical treatment.
Keywords: mucocele; sphenoid sinus; visual acuity